Interlimb asymmetries: are thresholds a usable concept? - Bishop, C. (Strength and Conditioning Journal, 2021)
The concept of thresholds has commonly appeared in the literature for the topic of interlimb asymmetry. However, with an abundance of literature showing asymmetry to be task- and metric-specific, the use of thresholds seems flawed. When computed, practitioners are often left with a percentage figure and it is not always entirely obvious how to interpret this value. This article aims to provide practitioners with some guidelines on meaningful ways to use and interpret interlimb asymmetry data.